Prevalence and recovery time of olfactory and gustatory dysfunctions of hospitalized patients with COVID-19 in Wuhan, China (2020)
Objectives: To investigate olfactory and gustatory dysfunction in patients with coronavirus disease 2019 (COVID-19) in Wuhan using a telephone interview. Methods: This retrospective telephone survey investigated 196 consecutive patients with COVID-19 discharged 3 months previously from two hospital in Wuhan, China. The characteristics of the patient's disease course and recovery time for olfactory and/or gustatory dysfunctions (OD and/or GD) were collected by telephone interview. Demographic data were collected from the patients’ medical records. Results: A total of 196 patients with COVID-19 completed the study. The most prevalent general symptoms consisted of fever, cough, and fatigue. 19.9% of patients reported OD and/or GD. In 87.2% of these cases, OD or GD appeared after the general symptoms. Among the patients, 51.4% had a recovery time of more than 4 weeks for OD and/or GD. Patients with COVID-19 and OD and/or GD had significantly higher rates of cardiovascular disease than patients without OD and/or GD (p = 0.002). Conclusion: Recovery from chemosensory dysfunction (OD and/or GD) was slow, with over half of the patients taking more than 4 weeks to recover. Cardiovascular disease might be related to the development of olfactory or taste disorders in patients with COVID-19.